Data driven differentiation in the standards-based classroom - Gregory, Gayle. 4 0 16; Kuzmich, Lin; 5 (Thousand Oaks, California : Corwin Press, 2004)
Contains a step-by-step guide that offers educators the tools for collecting, analyzing, and using data to design curriculum including instructional strategies that increase student learning and adjustable assignments for differentiated learning.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Standards. -- Individualized instruction.;Education;Curriculum planning.;Educational tests and measurements.;Individualized instruction; 20; 2